Phytochemical Screening and Toxicity Study of Saraca asoca Bark Methanolic Extract - Manas Kumar Mukhopadhyay; Debjani Nath (International Journal of Phytomedicine, 2011)
The study was conducted to screen for the phytochemicals constituents of bark of Saraca asoca (Roxb.), one of the folk medicinal plants found in West Bengal, Bangladesh and Sri Lanka. The acute and sub- acute toxicity of methanolic extract of S. asoca bark on mice was studied. Phytochemical analysis of S. asoca (bark) methanolic extract revealed the presence of high percentage of flavonoids and reducing sugar in addition with saponins, glycosides, steroids, anthraquinones and volatile oil. In mice, daily single oral doses of S. asoca methanolic extract (0.3 and 1.2 g/Kg body weight) were well tolerated and no adverse behavioral effect was found as used for 30 days (LD50=6.526 g/Kg for acute administration) and induced no significant changes in body and organs weights. However, hematological parameters showed a significant decrease in platelet count (432±98.3, p<0.05) when the dose is 1.2 g/Kg body weight in relation to control animals, suggesting disturbances in platelet production whereas no effect was found on serum biochemical parameters like serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT), serum alkaline phosphatase (ALP), and bilirubin, total protein, uric acid, urea, creatinin. This study indicates that Saraca asoca is nontoxic for both acute and sub-acute oral administrations.